INSTITUTIONAL FRAGMENTATION AS GOVERNANCE GAP: WHY INDONESIA HAS NOT ESTABLISHED A MARITIME FUSION CENTER IN THE ERA OF AI-AUGMENTED GIS (Journal Keamanan dan Keselamatan Maritim, 2026)
This study examines why Indonesia has not yet established a maritime fusion center in the era of AI-augmented GIS, despite facing critical maritime security threats such as IUU fishing, piracy, and cyber risks. Using a qualitative comparative case study design with a most-different systems approach, the research contrasts Indonesia with Singapore’s ReCAAP Information Sharing Centre (ISC). The analysis is triangulated through three theoretical frameworks: Kettl’s (2006) institutional fragmentation typology, McConnell’s (2010) policy failure framework, and Provan & Kenis’s (2007) network governance typology. The findings reveal that the absence of a maritime fusion center is not primarily a technological or budgetary failure but a governance failure. Indonesia’s maritime security architecture exhibits structural, informational, and political fragmentation that are mutually reinforcing. Bakamla operates as a coordinator without binding authority, whereas Singapore’s ISC functions as a network administrative organization (NAO) with a clear mandate. The most binding constraint is political fragmentation agencies defend information monopolies protected by legal ambiguity and lack of presidential-level political will. The study concludes that incremental technology-first approaches will fail; prior institutional reforms are necessary, including a presidential decree mandating data sharing, amendments to conflicting laws (UU No. 32/2014 and UU No. 34/2004), a maritime data governance framework, and ratification of the ReCAAP agreement.